SOME CONSIDERATIONS ON FOREIGN LANGUAGE SYLLABUS DESIGN - Norica-Felicia BUCUR (Challenges of the Knowledge Society)
Studies and articles that focus on describing and classifying foreign language syllabuses are dominated by the product / process dichotomy. Nevertheless, this is not always the case, as there are authors who, apparently, use other criteria to produce their own taxonomy. Thus, this paper attempts to provide a brief chronological outline of the various descriptions found in the syllabus design literature, so that the principles underlying the proposed taxonomies could be identified and critical comparisons could be performed.